Associations of single and multiple vitamin exposure with childhood eczema: data from the national health and nutrition examination survey - Wang, Fang; Wang, Xiaolie; Wang, Jiayan; Liu, Biqing (Frontiers in Pediatrics, 2024)
Aim The association between vitamins and eczema has garnered attention, yet few studies have evaluated the effects of co-exposure to multiple vitamins on this condition. This study aims to assess the association of vitamin mixtures with eczema in children. Methods This cross-sectional study analyzed data from 2,244 children aged 6–17 years from the National Health and Nutrition Examination Surveys. Eczema served as the primary outcome. Six serum vitamins, namely, vitamins A, B6, B12, C, D, and E, were the main variables. Weighted multivariate logistic regression was adopted to analyze the association between each serum vitamin and eczema. Odds ratios (OR) with a 95% confidence interval (CI) were calculated. Bayesian kernel machine regression (BKMR) analysis and the quantile g-computation (qgcomp) model were used to evaluate the association of co-exposure to multiple vitamins with eczema. Results In total, 10.83% of children (n = 243) developed eczema. After adjusting for confounding factors, we observed that compared with the reference group (vitamin B12 with second quartile), the OR for eczema was 0.604 (95% CI: 0.373–0.978, P = 0.041) for the first quartile of vitamin B12. Both BKMR analysis and the qgcomp model consistently showed that co-exposure to the six vitamins was positively correlated with the risk of eczema, with vitamin B6 contributing most to the overall effect. In BKMR analyses, we observed an interaction between vitamins B6 and B12 concerning eczema risk. Conclusion Co-exposure to vitamins A, C, B6, B12, D, and E was found to be associated with an increased risk of eczema in children, with vitamin B6 as the greatest positive contributor driving the overall effect.